Difference between revisions of "Distance formula"

m
(Cleaning up)
Line 2: Line 2:
  
  
{{stub}}
+
==Shortest distance from a point to a line==
 
 
--Shortest distance from a point to a line--
 
 
the distance between the line <math>ax+by+c = 0</math> and point <math>(x_1,y_1)</math> is
 
the distance between the line <math>ax+by+c = 0</math> and point <math>(x_1,y_1)</math> is
 
<cmath>\dfrac{|ax_1+by_1+c|}{\sqrt{a^2+b^2}}</cmath>
 
<cmath>\dfrac{|ax_1+by_1+c|}{\sqrt{a^2+b^2}}</cmath>
  
---Proof---
+
===Proof===
 
The equation <math>ax + by + c = 0</math> can be written as <math>y = -\dfrac{a}{b}x - \dfrac{c}{a}</math>
 
The equation <math>ax + by + c = 0</math> can be written as <math>y = -\dfrac{a}{b}x - \dfrac{c}{a}</math>
 
Thus, the perpendicular line through <math>(x_1,y_1)</math> is:
 
Thus, the perpendicular line through <math>(x_1,y_1)</math> is:

Revision as of 11:34, 22 October 2015

The distance formula is a direct application of the Pythagorean Theorem in the setting of a Cartesian coordinate system. In the two-dimensional case, it says that the distance between two points $P_1 = (x_1, y_1)$ and $P_2 = (x_2, y_2)$ is given by $d = \sqrt{(x_1 - x_2)^2 + (y_1 - y_2)^2}$. In the $n$-dimensional case, the distance between $(a_1,a_2,...,a_n)$ and $(b_1,b_2,...,b_n)$ is $\sqrt{(a_1-b_1)^2+(a_2-b_2)^2+\cdots+(a_n-b_n)^2}$


Shortest distance from a point to a line

the distance between the line $ax+by+c = 0$ and point $(x_1,y_1)$ is \[\dfrac{|ax_1+by_1+c|}{\sqrt{a^2+b^2}}\]

Proof

The equation $ax + by + c = 0$ can be written as $y = -\dfrac{a}{b}x - \dfrac{c}{a}$ Thus, the perpendicular line through $(x_1,y_1)$ is: \[\dfrac{x-x_1}{a}=\dfrac{y-y_1}{b}=\dfrac{t}{\sqrt{a^2+b^2}}\] where $t$ is the parameter.

$t$ will be the distance from the point $(x_1,y_1)$ along the perpendicular line to $(x,y)$. So \[x = x_1 + a \cdot \dfrac{t}{\sqrt{a^2+b^2}}\] and \[y = y_1 + b \cdot \dfrac{t}{\sqrt{a^2+b^2}}\]

This meets the given line $ax+by+c = 0$, where: \[a\left(x_1 + a \cdot \dfrac{t}{\sqrt{a^2+b^2}}\right) + b\left(y_1 + b \cdot  \dfrac{t}{\sqrt{a^2+b^2}}\right) + c = 0\] \[\implies ax_1 + by_1 + c + \dfrac{t(a^2+b^2)}{\sqrt{a^2+b^2}} + c = 0\] \[\implies ax_1 + by_1 + c + t \cdot \sqrt{a^2+b^2} = 0\]

, so: \[t \cdot \sqrt{a^2+b^2} = -(ax_1+by_1+c)\] \[\implies t = \dfrac{-(ax_1+by_1+c)}{\sqrt{a^2+b^2}}\]

Therefore the perpendicular distance from $(x_1,y_1)$ to the line $ax+by+c = 0$ is:

\[|t| = \dfrac{|ax_1 + by_1 + c|}{\sqrt{a^2+b^2}}\]

Invalid username
Login to AoPS